LANGUAGE, HUMAN DEVELOPMENT AND EDUCATION: FOCUS ON CHILDREN'S EDUCATION - Solange Maria Alves; Marilandi Maria Mascarello Vieira (Editora da Universidade de Santa Cruz do Sul, 2010)
Based on theoretical patterns of historical-cultural approach, this text proposes a critical discussion about the relation among the process of human development, the role of language and scholar education as elements of specific and intentional mediation, directed to the development of typical human ways of thinking, or, as preferred by Vygotsky, superior psychological functions. Under this focus, the author points some characteristics to be assumed by scholar organization, committed with pedagogic praxis for childhood, approaching the playful of social roles and the game as linguistic elements itself, and, thus, owners of social content, fundamental symbolic contents to be taken as start element for the educative action of change. KEYWORDS: Language and play. Human development. Education. Childhood. AUTORA